Dissecting the properties of neutron star-black hole mergers originating in dense star clusters - Arca Sedda, Manuel (Communications Physics, 2020)
The detection of gravitational waves emitted during a neutron star-black hole merger and the associated electromagnetic counterpart will provide a wealth of information about stellar evolution nuclear matter, and general relativity. While the theoretical framework about neutron star-black hole binaries formed in isolation is well established, the picture is loosely constrained for those forming via dynamical interactions. Here, we use N-body simulations to show that mergers forming in globular and nuclear clusters could display distinctive marks compared to isolated mergers, namely larger masses, heavier black holes, and the tendency to have no associated electromagnetic counterpart. These features could represent a useful tool to interpreting forthcoming observations. In the local Universe, gravitational waves emitted from dynamical mergers could be unraveled by detectors sensitive in the decihertz frequency band, while those occurring at the distance range of Andromeda and the Virgo Cluster could be accessible to lower-frequency detectors like LISA. The theoretical framework explaining the formation of a black hole-neutron start binary in isolation is well established, but little is known for the same phenomenon occurring in a denser environment as a star cluster. Using N-body simulations, the author models such complex interactions finding that the resulting binary systems may be quite different from isolated mergers and, with potentially no electromagnetic counterpart, they could be observed via gravitational waves with detectors sensitive at in decihertz frequency band.